2012
DOI: 10.1371/journal.pone.0031999
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Maturation of Dopaminergic Neurons Derived from Mouse Embryonic Stem Cells: Implications for Transplantation

Abstract: The obvious motor symptoms of Parkinson's disease result from a loss of dopaminergic neurons from the substantia nigra. Embryonic stem cell-derived neural progenitor or precursor cells, adult neurons and fetal midbrain tissue have all been used to replace dying dopaminergic neurons. Transplanted cell survival is compromised by factors relating to the new environment, for example; hypoxia, mechanical trauma and excitatory amino acid toxicity. In this study we investigate, using live-cell fluorescence Ca2+ and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…It is known that early in development the action of psychostimulants such as amphetamine has a paradoxical effect on the firing rate of dopamine neurons [72] and this effect could be interesting evidence of the changes of excitability and its regulation by dopamine in the transformation from inactive to active processing of action selection regulated by dopamine. Recent experiments in mice show that -currents are upregulated in DA neurons in culture [73] and this observation together with our reported findings suggests a state of rapid changes in excitability in SN DA neurons indicating that these neurons and perhaps all DA neurons in the midbrain undergo a process where they transition from a non-functional immature state to a functional mature one in the first month of postnatal life. Given all of these findings, it would be interesting to examine the effects of dopamine on the synaptic plasticity mechanisms at cortico-striatal synapses early in development.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that early in development the action of psychostimulants such as amphetamine has a paradoxical effect on the firing rate of dopamine neurons [72] and this effect could be interesting evidence of the changes of excitability and its regulation by dopamine in the transformation from inactive to active processing of action selection regulated by dopamine. Recent experiments in mice show that -currents are upregulated in DA neurons in culture [73] and this observation together with our reported findings suggests a state of rapid changes in excitability in SN DA neurons indicating that these neurons and perhaps all DA neurons in the midbrain undergo a process where they transition from a non-functional immature state to a functional mature one in the first month of postnatal life. Given all of these findings, it would be interesting to examine the effects of dopamine on the synaptic plasticity mechanisms at cortico-striatal synapses early in development.…”
Section: Discussionsupporting
confidence: 86%
“…It has been recently demonstrated that neuronal survivability and viability is directly related to a great extent on neuronal maturity, and relatively maturing neurons will have higher survivability in an environment in the host brain that is rich in excitatory amino acids and other debilitating factors resulting from oxidative stress and immunological responses to tissue trauma [19]. Since 10-days differentiated cultures showed a lower population of progenitors and a higher population of mature neurons as compared to 7-days differentiated cells (Figure S1), the latter was considered for transplantation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of cells in murine cultures will be mature at this point (Watmuff et al 2012); it is likely that human cells at day 20 are still maturing ( …”
Section: Typical Resultsmentioning
confidence: 99%